Case report: Diagnosis and treatment of delayed epidural pyogenic abscess after brain tumor operation: a report of 5 cases and review of the literature - Shen, HePing; Lin, YingCong; Chu, ZhengMin; Wang, GengHuan; Chu, WenLai (Frontiers in Surgery, 2023)
Diagnosis and treatment of delayed epidural pyogenic abscess after brain tumor operation: A report of 5 Cases and review of the literature Objective: To explore the clinical manifestations and treatment of delayed epidural pyogenic abscess after brain tumor surgery. Method: To retrospectively analyze the medical records of 5 patients with delayed epidural pyogenic abscess after brain tumor surgery in our hospital from January 2010 to December 2020, including clinical manifestations, laboratory results, imaging findings, treatment measures, prognosis, etc. The causes of epidural abscess were analyzed, and the treatment methods and prognosis were evaluated.Result: Among the 5 patients, there were 4 males and 1 female, aged 52-75 years. Three cases were gliomas and 2 cases were meningiomas.Four cases received postoperative radiotherapy, and 1 case had open frontal sinus during operation. None of the surgical incisions were infected. The time between the tumor surgery and the discovery of an epidural abscess was 1.5 to 24 months. All the 5 patients had headache, 1 case had fever, 2 cases had limb dysfunction. Three cases had elevated blood inflammatory markers. MRI-DWI showed restricted diffusion. All 5 patients underwent surgery, 4 patients had bone flap removed and 1 patient had bone flap retained. Bacterial culture was positive in 3 cases and negative in 2 cases. All the 5 cases were cured, followed up for 0.5-9 years, and no epidural abscess recurred.The clinical manifestations and laboratory results of delayed epidural pyogenic abscess after brain tumor surgery are not specific, but MRI-DWI has specificity. Postoperative radiotherapy for brain tumors and intraoperative opening of frontal sinus may be associated with delayed epidural pyogenic abscess. For patients with normal skin flap and not serious inflammation of bone flap, the bone flap can be attempted for preservation.